Application of an Electronic System to the Management of Medical Records - Marutha, Ngoako Solomon (Mousaion: South African Journal of Information Studies, 2019)
The management of functions in any sector including the healthcare sector is highly dependent on the application of electronic technology to achieve effective results and to give peace of mind to the organisation. The manual modus operandi for the management of medical records in healthcare institutions brings about many discrepancies that regularly result in chaos in healthcare services, which always affects patients negatively. This study sought to investigate the application of an electronic system for the management of medical records in the Limpopo province of South Africa to support healthcare services. The study used a survey questionnaire to collect quantitative data from a sample of 306 (49%) out of a total of 622 records management officials. The response rate was 70.9 per cent (217), and system analysis and observation were applied to augment the quantitative data. The study discovered that the electronic system has not yet been applied for the management of medical records in healthcare institutions but is only used for capturing the personal information and financial status of patients or for billing purposes, although records management modules were available in the same system, and that negatively affects healthcare services and patients directly. The study recommends the application or enhancement of the current business administration system for healthcare patients or the development of a new electronic system to cater for the electronic management of medical records to support healthcare service delivery. The study further proposes a framework for the application of an electronic system for the management of medical records to support healthcare service delivery.